Hubungan Media Customer Relationship Management Dengan Kepuasan Pelanggan pada Hotel Istana Nelayan - Chandra Wibowo Widhianto; Virgyne Livynia; Diana Ramadhany (Bina Nusantara University, 2003)
Facing comptetition in service company, especially hotels, must have the ability to give services in order to satisfy the customer. Customer Relationship Managemen (CRM) is one of communication media between company and customer that profitable for both side. This research try to find out how big the connection between Customer Relationship Managemen (CRM) with customer satisfaction in Istana Nelayan Hotel. The result is there is significant connection between media with customer satisfaction in Istana Nelayan Hotel.